The New Strategy of Nike Corporate Communication in Efforts to Build a New Corporate Image - Dani Fadillah; Dong Hao; Bai Long (Ikatan Sarjana Komunikasi Indonesia, 2021)
This study aims to examine the uniqueness of the corporate communication carried out by Nike when the well-known brand competes to sign a contract with athletes who reach their peak performance to promote its apparel. However, Nike signs contracts with players when they are still rising stars and then leaves them. Nike does something that well-known brands do not usually do. Normally, they compete to attract stars who are in their golden age. This research was conducted using a qualitative approach through case study research. The materials of this research were obtained by conducting a literature review, matters related to the Nike author's boredom collected from various sources, and reviewed using corporate communication logic. The results of this study indicate that Nike's steps are aimed at creating a new impression without leaving the old self-image.